Risk Management in Banking Institutions: Comparison between Developed and Developing Countries - Wang, Han (2007)
Uncertainty makes economic and business environment more complex than ever. This is especially true for financial institutions that face substantial financial volatility and shocks, especially those with substantial debt and commodity price exposures. Thus risk management in financial sectors has been absorbing more and more attention all over the world in recent decades. A content analysis of 12 leading banks' annual reports undertook to reveal the development trend of risk management in developed countries and to examine the deficiency in developing countries. Moreover, the comparison in risk management systems is made between developed and developing countries. In doing so, the reasons of disparity are highlighted and advices are contributed to developing countries for future improvement. Hoping this research will be of some help to the financial institutions of less developed country at such a critical moment.